Perancangan Tempat Sampah Pembuka Tutup Otomatis dan Indikator Kapasitas - Arsa Priyo Rahardjo; Suraidi Suraidi; Hadian Satria Utama (Universitas Tarumanagara, 2018)
Trash bins are available in various places, but many people are still littering. Trash dumped carelessly can cause unpleasant odors, germs and bacteria that cause illness. To revive the public, several bins are made as attractive as possible to increase public interest to dispose trash in place. The trash designed can open the cover automatically, detects the incoming trash and trash detecting capacity when fully filled. When the trash is put in the trash bin, it will be detected and will be immediately issued to the sounds stored via MP3 module that sound